Aninhamento da metacomunidade de invertebrados bentônicos em áreas alagáveis Neotropicais. - Pinha, Gisele Daiane (2016)
On the metacommunity context, the distribution pattern known as species nestedness is highlighted from others because it is commonly observed for the most diverse biological communities. Three different ways to link the nested distribution pattern of invertebrates metacommunity in relation to the most important environmental conditions for the assembly of this group in flooding sites were applied. We compared the nestedness of benthic invertebrates metacommunity in multiple sites in relation to variances found in the environmental heterogeneity of two different hydrological periods. We reported the importance of Chironomidae metacommunity nestedness to the environmental conservation in long-term researches, comparing this distribution pattern to variations in the fluviometric levels. We compared the functional responses of lacustrine species in relation to variances in the environmental similarity promoted by flood and drought events. The level of habitat heterogeneity from the floodplain was highly dependent with fluviometric level, i.e., it was temporally dynamic and, moreover, it was important to predict the nestedness level of a metacommunity. The variations in both habitat heterogeneity and fluviometric levels, were able to change not only the taxonomic composition of Chironomidae metacommunity but also to change the functional structure and the abundance relationships of this group. Nestedness was not a good measure to evaluate changes in the community structure when we considered the high organization level. We were able to detect environmental gradients where different habitats encompassed the highest species richness. The results raise the nestedness importance as a tool for environmental conservation and highlight the importance of maintenance of different habitats in a floodplain through time.